Optimizing pretreatment blanching process of browning, total phenol, and DPPH scavenging capacity in cocoa pod husk - Anoraga, Satria Bhirawa; Shamsudin, Rosnah; Hamzah, Muhammad Hazwan; Sharif, Suzannah; Saputro, Arifin Dwi; Mohd Basri, Mohd Salahuddin (Springer Science and Business Media Deutschland GmbH, 2025)
Blanching brightens cocoa pod husk (CPH) but causes leaching and loss of nutrients. This research aims to optimize blanching conditions, investigate the impacts of temperature and blanching time on browning index, DPPH scavenging capacity, and total phenol content, and compare blanching with steam blanching and nontreatment methods. Blanching parameters, including temperature (50 °C–90 °C) and time (3–15 min), were optimized through response surface methodology by using a central composite design (CCD). The optimum blanching conditions (90 °C and 12.5 min) generated a browning index of 11.23, total phenol content of 322.73 mg gallic acid equivalents (GAE)/g, and DPPH scavenging capacity of 127.92 mg Gallic acid equivalent antioxidant capacity (GAEAC)/g, resulting in a desirability value of 0.89. Blanching with hot water produced CPH powder with a low browning index and high water-holding and swelling capacities. CPH powder produced by hot-water blanching had higher total phenol content and DPPH scavenging capacity than that produced by steam blanching but had slightly lower total phenol content and DPPH scavenging capacity than untreated CPH powder because of leaching. These findings suggest that optimized blanching conditions can improve CPH's functional properties such as fiber content and DPPH scavenging capacity, supporting its potential as a fiber-rich food ingredient. Future studies should explore additional processing techniques to enhance nutrient retention and broaden its applications in functional food formulations.